Transmission dynamics of tuberculosis in a high-incidence country: prospective analysis by PCR DNA fingerprinting - Haas, Walter; Engelmann, Guido; Amthor, Beate; Shyamba, S.; Mugala, F.; Felten, Michael; Rabbow, M.; Leichsenring, Michael; Oosthuizen, O. J.; Bremer, Hans J. (Journal of clinical microbiology, 1999)
We have prospectively analyzed the DNA fingerprints ofMycobacterium tuberculosis strains from a random sample of patients with newly diagnosed tuberculosis in Windhoek, Namibia. Strains from 263 smear-positive patients in whom tuberculosis was diagnosed during 1 year were evaluated, and the results were correlated with selected epidemiological and clinical data. A total of 163 different IS6110 fingerprint patterns were observed among the 263 isolates. Isolates from a high percentage of patients (47%) were found in 29 separate clusters, with a cluster defined as isolates with 100% matching patterns. The largest cluster included isolates from 39 patients. One predominant strain of M. tuberculosiscaused 15% of cases of smear-positive pulmonary tuberculosis in Windhoek. That strain was also prevalent in the north of the country, suggesting that in contrast to other African countries with isolates with high levels of diversity in their DNA fingerprint patterns, only a restricted number of different strains significantly contribute to the tuberculosis problem in Namibia.
Gesehen am 21.12.2020